Automatic evaluation of sports motion: A generic computation of spatial and temporal errors - Morel, M.; Achard, C.; Kulpa, R.; Dubuisson, S. (Image and Vision Computing, 2017)
In this paper, we propose an innovative automatic evaluation process for any sport motions. Based on a 2-level Dynamic Time Warping, the process allows the evaluation of both spatial and temporal errors of a novice motion based on an experts' motion database and without any prior knowledge on the sport. This new methodology is evaluated with regards to coaches' assessment on two different kinds of motions: tennis serves and karate tsuki.